2016
DOI: 10.1016/j.rmed.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of interstitial lung disease in anti-Jo-1 positive antisynthetase syndrome

Abstract: We present a large cohort of anti-Jo-1 positive AS syndrome with ILD and note good overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 27 publications
6
72
0
2
Order By: Relevance
“…In other words, even in ARS-ILD patients showing a good response to initial therapy, pulmonary function frequently deteriorated during long-term follow-up. In terms of survival, only 2 patients died within 5 years from the ARS-ILD diagnosis and the 5-year survival rate was 97.0%, which indicates relatively good survival of ARS-ILD patients, similar to that reported in previous studies [6, 7]. Importantly, some patients with ARS-ILD suffered from refractory ILD over the long run, which led to a number of adverse events such as the necessity of home oxygen therapy and side effects related to the inability to reduce the dose of corticosteroids (e.g., muscle weakness, opportunistic infection, and diabetes mellitus).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In other words, even in ARS-ILD patients showing a good response to initial therapy, pulmonary function frequently deteriorated during long-term follow-up. In terms of survival, only 2 patients died within 5 years from the ARS-ILD diagnosis and the 5-year survival rate was 97.0%, which indicates relatively good survival of ARS-ILD patients, similar to that reported in previous studies [6, 7]. Importantly, some patients with ARS-ILD suffered from refractory ILD over the long run, which led to a number of adverse events such as the necessity of home oxygen therapy and side effects related to the inability to reduce the dose of corticosteroids (e.g., muscle weakness, opportunistic infection, and diabetes mellitus).…”
Section: Discussionsupporting
confidence: 87%
“…The HRCT patterns were classified into nonspecific interstitial pneumonia (NSIP), organizing pneumonia (OP), usual interstitial pneumonia, and NSIP with OP overlap according to previous reports [6, 15]. NSIP with OP overlap was identified when consolidations were superimposed on a background of ground-glass opacity (GGO) with or without reticulations or traction bronchiectasis [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interstitial lung disease is a common extra-muscular complication of idiopathic inflammatory myopathies, and low-diffusing capacity for carbon monoxide (DLCO) is known to increase the risk of mortality [1, 2]. A recent study demonstrated that recovery of skeletal muscle strength and reduced creatine kinase levels by medication for idiopathic inflammatory myopathies may improve forced vital capacity (FVC) due to muscular strength reinforcement; however, DLCO and interstitial infiltrates on CT were not ameliorated in most cases [3].…”
Section: Introductionmentioning
confidence: 99%
“…Questionnaires for chronic lung disease have been developed to evaluate the symptoms and the Chronic obstructive pulmonary disease Assessment Test (CAT) [1] has been adapted for interstitial lung disease [2]. Cross-sectional studies reported the relationship between the CAT score and the results of pulmonary function tests for interstitial lung disease, and found that higher CAT scores and/ or lower diffusion capacity of the lungs for carbon monoxide (D LCO ) significantly predicted mortality [3,4].…”
Section: Introductionmentioning
confidence: 99%